1997
DOI: 10.1111/j.1432-1033.1997.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Organization of A Multifunctional Polyketide Synthase Involved in the Biosynthesis of the Macrolide Immunosuppressant FK506

Abstract: The immunosuppressant FK506 is a 23-membered macrocyclic polyketide produced by several Streptomyces species. Sequencing of a 19.5-kb contiguous segment of DNA from the FK506 gene cluster of Streptomyces sp. MA6548 revealed the presence of a single 19.3-kb open reading frame designatedfkbA. fkbA encodes a component of the FK506 polyketide synthase, a complex enzyme system which catalyzes synthesis of the polyketide portion of FK506. The predicted product of genefkbA is a 630660-Da protein (6420 amino acids) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
67
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 33 publications
1
67
0
1
Order By: Relevance
“…Initial comparison of the biosynthetic gene clusters for rapamycin (15)(16)(17), FK506 (26,27), and FK520 (28) did not reveal obvious candidate genes encoding the enzymes of such a pathway. However, detailed genetic analysis has since revealed an essential role for rapK in the production of DHCHC during rapamycin biosynthesis (29).…”
mentioning
confidence: 99%
“…Initial comparison of the biosynthetic gene clusters for rapamycin (15)(16)(17), FK506 (26,27), and FK520 (28) did not reveal obvious candidate genes encoding the enzymes of such a pathway. However, detailed genetic analysis has since revealed an essential role for rapK in the production of DHCHC during rapamycin biosynthesis (29).…”
mentioning
confidence: 99%
“…In this context, we also have to consider that FadD33 is similar to the putative polyketide biosynthesis protein PKSJ of Bacillus subtilis (Albertini et al, 1995), as it shows a 27n1 % identity in an overlap of 468 aa (http :\\ genolist.pasteur.fr\TubercuList\). As microbial polyketide metabolites have shown potent biological activities in different models, acting as virulence factors, antibiotics, immunosuppressants and toxins (George et al, 1999 ;Kolattukudy et al, 1997 ;Motamedi et al, 1997), it is tempting to consider that mycobacterial FadD33 might be involved in the synthesis of polyketides that play a role in M. tuberculosis infection in the liver. The involvement of certain polyketide metabolites in M. tuberculosis infection has been reported by Graham & Clark-Curtiss (1999), who showed that pks2, one of the 18 polyketide synthase genes of M. tuberculosis H37Rv, is expressed in infected human macrophages but not in bacteria growing in culture broth, and by De Voss et al (2000), who demonstrated that the mycobactin siderophores produced by polyketide synthase enzymes are essential for M. tuberculosis growth in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…strain ATCC 55098 (MA6858) (26), Streptomyces sp. strain ATCC 53770 (MA6548) (25), and S. tsukubaensis NRRL 18488 (8). Recently, the sequences of the entire FK506 biosynthetic gene clusters from Streptomyces sp.…”
mentioning
confidence: 99%